Selected Publications in Nanomaterials Science and Engineering - Carey, David (Trinity College Dublin, School of Engineering, Electronic & Electrical Eng, 2025)
This submission for a ScD degree is based on a selection of 69 publications grouped into the themes of Electrical Transport in Nanomaterials (23 papers, group A), Structural and Electronic Properties of Nanomaterials (26 papers, group B) and Functional Nanomaterials: Growth, Processing and Characterisation (20 papers, group C). These three thematic areas have been selected as they broadly reflect the “Structure-Property” relationships of the materials studied. Within each group, the publications are listed chronologically starting with the oldest; reference A1 refers to paper 1 in group A etc. As per submission guidelines a small number of papers have been selected, section 2, with a commentary of about 1,000 words, to showcase the contribution and impact to the field. By the nature of nanomaterials research, these selected publications cross the traditional subject disciplines of electronic engineering, condensed matter physics, materials science and chemistry. Much of the research also has been done in collaboration with academic colleagues within Surrey, nationally and internationally, as well as with talented graduate students.
Keywords: Electrical Transport in Nanomaterials; Structural and Electronic Properties of Nanomaterials; Functional Nanomaterials: Growth, Processing and Characterisation